ASSESSMENT OF BIODIVERSITY AND RELATIVE ABUNDANCE OF FISH AT TIGA RESERVOIR, KANO: CURRENT STATUS - AUDU, R; BUKAR, A.A.; USMAN, B.I. (Nigerian Journal of Fisheries, 2022)
A study on the diversity and relative abundance of fish was conducted to determine their current status at Tiga Reservoir, Kano State, Nigeria.. The fish specimens were collected from three landing sites (Tiga, Rurum and Tarmai) between 8:00 – 11:00am with the help of artisanal fishermen using various assorted fishing gears (monofilament and multifilament gill nets). They were collected monthly from Nov. 2018 to Oct. 2019. The Relative abundance and biodiversity indices were calculated. The result shows that the reservoir harbours seventeen (17) species of fish belonging to ten (10) families, six (6) orders and seventeen (17) genera. The family Cichlidae is represented by four (4) species, the family Mormyridae is represented by three (3) species, the family Claroteidae and Alestidae each comprises of two (2) species while the family Bagridae, Clariidae, Malapteruridae, Protopteridae, Schilbedae and Cyprinidae are each represented by one (1) specie only. The most dominant family is the Cichlidae (31.36%) followed by the family Claroteidae (16.24%) and family Mormyridae (14.34%). The least is the family Protopteridae (0.03%). The most dominant species is the Coptodon zilli making up about 16.77% followed by Bagrus bajad (13.29%) while the least specie is Protopterus annectens (0.03%). Shannon weiner index (H) and Simpson index (D) of 4.0021 and 0.21903 at Site I showed that the fish were more diverse at Site I than Site II and III. Chi square (13.13) reveals a significant difference at the sites (p<0.05). This study provides an up-to-date information on the current status of Tiga reservoir with respect to the biodiversity and relative abundance of the fish species. There is the need for a frequent assessment of fish stock because population size, structure and distribution fluctuate in response to environmental variation.